2023
DOI: 10.3390/ijerph20031848
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Relationship of Meteorological Factors and Severe Pediatric Respiratory Syncytial Virus (RSV) Infection in Central Peninsular Malaysia

Abstract: Respiratory syncytial virus (RSV) is the most common pathogen causing viral respiratory tract infections among younger children worldwide. The influence of meteorological factors on RSV seasonal activity is well-established for temperate countries; however, in subtropical countries such as Malaysia, relatively stable temperate climates do not clearly support this trend, and the available data are contradictory. Better understanding of meteorological factors and seasonality of RSV will allow effective strategic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…As suggested by Räsänen [ 29 ], the connection between seasonal epidemiology and human behavior, considering factors such as holiday seasons versus school and daycare periods, which involve increased indoor crowding and the use of public transportation. The complex interplay between rainfall patterns, local geography, sanitation infrastructure, and human behavior makes it challenging to draw definitive conclusions regarding the direct relationship between rainfall and diarrheal disease incidence [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…As suggested by Räsänen [ 29 ], the connection between seasonal epidemiology and human behavior, considering factors such as holiday seasons versus school and daycare periods, which involve increased indoor crowding and the use of public transportation. The complex interplay between rainfall patterns, local geography, sanitation infrastructure, and human behavior makes it challenging to draw definitive conclusions regarding the direct relationship between rainfall and diarrheal disease incidence [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our latest epidemiological study, we identified two peaks of RSV seasonality occurring in distinct monsoon periods, specifically during July to August and October to December, coinciding with previous local and regional studies. ( 10 , 25–27 ). Surprisingly, in this study, we observed an unusual increase of RSV cases throughout the first half of 2021.…”
Section: Discussionmentioning
confidence: 99%
“…This is deemed as a global phenomenon as many countries reported a change in the seasonal variation of RSV during the COVID-19 pandemic ( 28 ). Typically, RSV infections peak during colder temperatures and reduced humidity, conditions favorable for the stability and transmission of the virus ( 10 ). However, in Shanghai, China, Ran Jia et al documented an unusual increase in the RSV detection rate during the summer of 2021 ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations